Unconventional Computing Catechism - Teuscher, Christof (Frontiers in Robotics and AI, 2014)
What makes a new paradigm or technology promising? What should science, research, and industry invest money in? Is there a life after CMOS electronics? And will the vacuum tube be back? While one cannot predict the future, one can still learn from the past. Over the last decade, unconventional computing developed into a major new research area with the goal to look beyond existing paradigms. In this Perspective we will reflect on the current state of the field and propose a set of questions that anyone working in unconventional computing should be able to answer in order to assess the potential of new paradigms early on.